Association of Subclinical Hypothyroidism With Anxiety Symptom in Young First-Episode and Drug-Naïve Patients With Major Depressive Disorder - Yang, Ruchang; Du, Xiangdong; Li, Zhe; Zhao, Xueli; Lyu, Xiaoli; Ye, Gang; Lu, Xinchuan; Zhang, Guangya; Li, Chuanwei; Yue, Yan; Wu, Yuxuan; Peng, Ruijie; et al. (Frontiers in Psychiatry, 2022)
Backgrounds: Subclinical hypothyroidism (SCH) was reported to be associated with depression; however, its role in coexisting anxiety in young patients with major depressive disorder (MDD) remains unclear. The objective of this study was to explore the relationship between SCH and anxiety symptoms in young first-episode and drug-naïve (FEDN) MDD patients. Methods: A total of 520 outpatients diagnosed as FEDN MDD with SCH were recruited in this study. Their socio-demographic, clinical data and thyroid function parameters were collected. The Hamilton Anxiety Rating Scale (HAMA) and the Hamilton Depression Rating Scale (HAMD) were employed to measure anxiety and depressive symptoms, respectively. Results: The prevalence rate of anxious major depressive disorder (A-MDD) was 15.8% in young FEDN MDD patients with comorbid SCH. Moreover, serum thyroid stimulating hormone (TSH) levels were significantly higher in patients with A-MDD compared with those with non-anxious MDD (NA-MDD) (p<0.001). Binary logistic regression analysis indicated that A-MDD was associated with serum TSH levels with an odds ratio (OR) of 1.602. A-MDD and NA-MDD were able to be distinguished by serum TSH level, where ≥6.17mIU/L was defined as a positive diagnosis of A-MDD. There were no significant differences between NA-MDD and A-MDD patients in terms of socio-demographic variables, serum free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidases antibody (TPOAb) and anti-thyroglobulin (TgAb) levels. Conclusions: Serum TSH level may be a promising biomarker of moderate and severe anxiety symptoms in young FEDD MDD patients with SCH, suggesting the importance of assessing serum TSH level for anxiety prevention and rehabilitation.